VIG ISTVÁN: HORVÁT NYELVTAN: Budapest: ELTE, BTK Szláv Filológiai Tanszék, 2008. (Opera Slavica Budapestinensia, Linguae Slavicae). 356 o. - Pátrovics, Péter (Slavia Centralis, 2020)
VIG ISTVÁN: HORVÁT NYELVTANIn the article, author presents and evaluates the work of István Vig, Horvát Nyelvtan (Croatian Grammar).
Keywords: István Vig; Horvát Nyelvtan; Croatian Grammar; review